Giro Jampa: proposição do uso de serious games para reabilitação de pacientes com lesão medular - Braga, Marieliza Araújo (2021)
Spinal cord injury is a damage that affects the spinal canal, partially or totally, causing motor and sensory comorbidities. Such damage promotes a decrease in functional independence and psycho-emotional consequences secondary to physical limitations. For functional treatment, the rehabilitation process is essential, with a range of conventional techniques. Serious games are often used as an alternative prescription tool in the rehabilitation process, in a playful, innovative and effective way. Considering the needs of individuals diagnosed with spinal cord injury, and respecting the basic requirements for composing a serious game, GiroJampa was developed, aimed at motor rehabilitation and improvement of psycho-emotional aspects of individuals with thoracolumbosacral spinal cord injury, wheelchair users, using a model of decision making to balance difficulty and user performance evaluation. GiroJampa is an application developed on the motor engine Unity 3D, consisting of an aesthetic that refers to the beachfront of the city of João Pessoa/PB, having three levels of difficulty (beginner, intermediate and advanced), and presenting the development and implementation as a differential. of a decision-making model based on conditional logic rules, which receives the input data sent by the sensor coupled to the wheelless ergometer, processes and generates a response with the evaluation of the user's performance and balancing the level of difficulty, in addition to the implementation of the Borg's Perceived Exertion Scale for Perceived Exertion monitoring.